Neurological disorders: towards a mechanistic understanding of restless legs syndrome. - Shaw, P.J.; Duntley, S.P. (Current Biology, 2012)
Restless legs syndrome is a curious neurological disorder of unknown aetiology. A new study has found that Drosophila mutants in the fly homologue of a human gene, BTBD9, that has been implicated as a risk factor for restless legs display important features of the syndrome.